Study on the Fire Resistance of Axially Restrained H-Shaped Steel Beams Under Real Fire - Wenwen Chen; Qinghe Qin; Xiaoming Wang; Jie Li; Meng Liang; Zhihao Chen; Taochun Yang (Applied Sciences, 2025)
The fire resistance performance of steel beams is of utmost importance to the fire safety of building structures and personnel evacuation. To address the deviation in the assumption of uniform temperature distribution in traditional studies, this study conducted multiple simulation tests. It was found that when the size of the vent was reduced by 50%, the difference in the heating rate in the early stage of the fire was 30% to 50%. Increasing the load ratio from 0.2 to 0.8 can significantly reduce the critical temperature of the steel beam by 15% to 20%, and the corresponding critical temperature is reduced from 670 °C to 565 °C. Based on parametric analysis, a simplified evaluation model of critical temperature for Q460 high-strength steel beams is proposed. The calculation error of the model is less than 5%, which provides a theoretical basis for the whole process of fire protection design. The research achievements break through the limitations of traditional methods and offer innovative approaches to predicting the fire resistance performance of steel beams and their optimized design.